Do consumers value food products containing upcycled ingredients? The effect of nutritional and environmental information. (July 2021) - Asioli, Daniele; Grasso, Simona
Highlights: 430 UK consumers chose biscuits containing a conventional or an upcycled ingredient. Nutritional and environmental information of the upcycled ingredient were provided to consumers. Nutritional and environmental information similarly increased consumers' WTP. Implications for upcycled food businesses and policy makers were provided. Abstract: This study was the first to use a ranking experiment to estimate the effect of nutritional and environmental information on UK consumers' willingness to pay (WTP) for biscuits containing an upcycled ingredient, namely, defatted sunflower cake flour. Informing consumers about the nutritional and/or environmental benefits of the upcycled ingredient resulted in a significant increase in their WTP for this new food. Moreover, we found that nutritional and/or environmental information similarly affected individual WTP distributions for the upcycled ingredient towards more positive values. Our findings have important implications for product development and marketing strategies of upcycled food businesses.